2000
DOI: 10.1111/j.1740-8261.2000.tb01472.x
|View full text |Cite
|
Sign up to set email alerts
|

Duplex‐ultrasonographic Evaluation of the Common Carotid Artery in the Resting, Sedated and Anesthetized Horse

Abstract: The aim of this study was to determine the blood flow in the carotid artery during halothane anaesthesia by means of duplex-sonography. Seventeen warm blood horses were evaluated in dorsal and lateral recumbency and the results were compared with the values of the same horses resting and under sedation. The cross sectional area of the vessels, the time-averaged maximal blood velocity, time-averaged maximal blood flow and the resistance index were determined and the flow profile was evaluated. During halothane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
1
10
0
1
Order By: Relevance
“…Nevertheless, previously published data reported a decrease in SAP [2,20,23] and an increase in DIAM [6,24], which is consistent with the observed increase of CIRC, SURF, and DIAM and the reported vasodilator effect of ACP [25]. An augmentation of VF, reported after administration of ACP to healthy horses [6,2,25], is due to an increase in vessel DIAM, an increase in maximal flow velocity, and a decrease in peripheral resistance [26]. This is in agreement with the measured increase in PSV and decrease in RI in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, previously published data reported a decrease in SAP [2,20,23] and an increase in DIAM [6,24], which is consistent with the observed increase of CIRC, SURF, and DIAM and the reported vasodilator effect of ACP [25]. An augmentation of VF, reported after administration of ACP to healthy horses [6,2,25], is due to an increase in vessel DIAM, an increase in maximal flow velocity, and a decrease in peripheral resistance [26]. This is in agreement with the measured increase in PSV and decrease in RI in our study.…”
Section: Discussionsupporting
confidence: 91%
“…2,3 In those studies, blood flow patterns were evaluated in standing nonsedated horses 2,3 as well as in horses that were sedated or anesthetized. 3 Determination of compressibility, filling, and respiration-dependent movement of the vessel wall are the most important aspects of clinical examination of the jugular vein in humans. 4 Uninterrupted venous blood flow is hemodynamically modulated by respiration and characterized by a lack of appreciable retrograde flow peripherally.…”
mentioning
confidence: 99%
“…There are studies regarding B-mode and Spectral Doppler ultrasonography in the common carotid arteries of horses (Cipone et al 1997, Schmucker et al 2000, Aguiar 2015), but a review of the literature revealed no such studies involving mules. Unlike the results reported in the literature, this study did not observe differences between each side of the carotids in horses.…”
Section: Discussionmentioning
confidence: 99%
“…There are several types of studies on the common carotid artery in domestic horses (Cipone et al 1997, Schmucker et al 2000, as well as other animals such as dogs (Hess et al 2003, Calderon-Arnulphi et al 2011, sheep (Khamas et al 1984, Valentine et al 2011, cows (Braun & Föhn 2005, Gregory et al 2012, camels (Abdel-Magied & Drommer 1989, Kiełtyka-Kurc et al 2014 and even buffaloes (Prakash & Rao 1976, Gregory et al 2008, Sangwan et al 2015. However, studies on carotid artery ultrasound are few in the literature, especially in mules.…”
Section: Introductionmentioning
confidence: 99%